Recanalization of atherosclerotic stenosis and occlusion of intracranial vertebrobasilar artery - Zhi-Long Zhou; Liang-Fu Zhu; Tian-Xiao Li; Bu-Lang Gao (IBRO Neuroscience Reports)
Intracranial vertebrobasilar atherosclerosis is one of the major causes of posterior circulation ischemic strokes and may result in a high risk of recurrent stroke. Current treatment for vertebrobasilar stenosis comprises aggressive medication and percutaneous transluminal angioplasty and stenting (PTAS). Endarterectomy and intracranial-extracranial bypass surgery may be considered for large artery stenosis in the anterior circulation, but they may be deterred by some technical difficulties and great complication rates in the vertebrobasilar stenoses. PTAS may be good for eliminating the arterial stenosis and preventing recoil of arterial wall after balloon angioplasty alone, however, higher peri-procedural complications and poor follow-up outcomes prevent PTAS as a common treatment strategy. Nonetheless, for selected patients with severe (≥70 %) stenosis and non-acute occlusion of the intracranial vertebrobasilar artery refractory to the best medication, PTAS may be feasible, safe and effective if the treatment approaches and endovascular devices were tailored to the clinic-radiological features of each lesion and patient. Sub-satisfactory stenting recanalization of the stenosis using a balloon < 80 % of the diameter of the nearby normal artery for dilatation of the stenosis and selection of softer and more flexible stents and delivery systems may be advantageous in decreasing the peri-procedural complications. This study reviewed the concept of intracranial vertebrobasilar atherosclerotic stenosis, available treatment modalities, peri-procedural complications, risk factors for endovascular treatment and prognosis, evidence for sub-satisfactory recanalization of the stenosis, and strategies to improve the peri-procedural complications and prognosis with the hope of improving the treatment outcome of endovascular recanalization.